The causes, consequences, and solutions of Afghan migration to foreign countries (Case Study: Farah Province) (Salam International Academic Journal, 2025)
ghan migration has become a serious phenomenon driven by global conflicts, political instability, economic challenges, natural disasters, and climate change—factors that have significantly intensified over recent decades. This study analyzes the main causes, consequences, and practical solutions related to Afghan migration.The importance of this research lies in the fact that migration perpetuates Afghanistan’s economic, social, and political problems, while also impacting the economic, social, and cultural structures of host countries. Moreover, the study focuses on the long-term effects of migration and explores strategies to reduce it in support of Afghanistan’s development.The main objective of the research is to analyze the causes and consequences of migration and to propose practical recommendations for its reduction. The core research question is: "What economic, political, social, and environmental factors drive Afghan migration, and what are its outcomes?"Data were collected from a sample of 385 respondents using a questionnaire and analyzed using SPSS software. The results of statistical tests, including Pearson correlation (r = 0.75), ANOVA (p < 0.05), Cronbach’s alpha (α = 0.85), and multiple regression analysis, indicate that unemployment (β = 0.55), poverty (β = 0.47), political instability (β = 0.60), and climate change (β = 0.38) are the primary drivers of Afghan migration.Furthermore, the consequences of migration include a 10% increase in GDP for host countries, but it also leads to social issues and cultural tensions. The findings suggest that reducing Afghan migration requires strengthening security, fostering economic development, creating job opportunities, and enhancing cooperation with international organizations such as UNHCR and IOM. These measures can help mitigate the negative impacts of migration and provide sustainable solutions.
Keywords: Climate Change; Unemployment; Political Instability; Poverty; Migration